Effects of short-term low- and high-carbohydrate diets on postprandial metabolism in non-diabetic and diabetic subjects. - Culling, K; Neil, H; Gilbert, M; Frayn, K (2009)
BACKGROUND AND AIM: Low-fat high-carbohydrate diets raise plasma triacylglycerol (TG) concentrations. To test whether the nature of the carbohydrate affects metabolic responses, we conducted a randomized cross-over study using a short-term, intensive dietary modification. METHODS AND RESULTS: Eight non-diabetic subjects and four subjects with diet-controlled type 2 diabetes participated. They followed three isoenergetic diets, each for 3 days: high-fat (50% energy from fat), high-starch and high-sugar (each 70% energy from carbohydrate). Normal foods were provided. We measured plasma TG and glucose concentrations, fasting and after a standard test meal, on day 4 following each dietary period. Fasting TG concentrations were greatest following the high-sugar diet (mean+/-SEM for all subjects 1900+/-420micromol/l) and lowest following high-fat (1010+/-130micromol/l) (P=0.001); high-starch (mean 1500+/-310) and high-fat did not differ significantly (P=0.06). There was a greater effect in the diabetic subjects (diet x diabetes status interaction, P=0.008). Postprandial TG concentrations were similarly affected by prior diet (P<0.001) with each diet different from the others (P